Dengue Outbreak in a Hilly State of Arunachal Pradesh in Northeast India. (21st January 2014) - Khan, Siraj A.; Dutta, Prafulla; Topno, Rashmee; Soni, Monika; Mahanta, Jagadish
Abstract : Dengue has been reported from plains as well as hilly regions of India including some parts of Northeast India. In July-August 2012, outbreak of fever with unknown origin (FUO) indicative of Dengue was reported in Pasighat, East Siang district of Arunachal Pradesh (AP) state. Serum samples ( n = 164) collected from patients from Health Training and Research Centre General Hospital, Pasighat, were tested for NS1 antigen and IgM antibodies. NS1-positive samples were analyzed by RT-PCR assay and entomological surveys were carried out. The majority of suspected cases reported NS1 antigen positivity. Females and young adults were mostly affected. The majority of the amplified NS1-positive samples showed Dengue serotype 3 infection. Aedes (Stegomyia) albopictus, known as semiurban breeding mosquitoes, was the only potential vector species identified from the affected areas of Pasighat which single handedly contributed to the outbreak. Thus, the present work identifies Dengue as an emerging arboviral infection in hilly state of AP along with a looming risk of its spread to neighbouring areas.